The Effect of Adding Beta-glucan Extracted From Bread yeast and barley bran on Inhibiting Microbial Population of Fish Patties at Cooling Storage Periods - Al-Jumaiee, Shaymaa A.J.; Al-Manhel, Alaa J.A.; Al- Hussainy, Khadeeja S.J. (Iraqi Journal of Aquaculture, 2022)
The Homopolysaccharide called beta-glucan was extracted from different sources, microbial source (baking yeast of Turkish origin) and vegetable source (brown barley bran) using the classical method and hot water method respectively. Results showed that the higher yield contents of β-glucan, which reached 5.95 % and 5.18 % were found in the baker’s yeast of Turkish origin and barley bran respectively, The β-glucan was analyzed by Fourier transform infrared spectroscopy (FT-IR) and the result confirmed that the extracted glucan showed a high degree of similarity and purity as compared with the standard, The β-glucan was added to the fish patties at different ratio (0, 0.1, 0.3, 0.5, 1) gm\25gm patties, and storage patties at 4 °C for 14 days. Effect of addition of different levels of β-glucan from both sources on inhibition of the bacterial counts for fish patties during storage (14 days) was studied, the total counts of bacteria was decreased with increasing the ratios of β-glucan up to 1%, the ability of the extracted β-glucan from barley bran to inhibit the total bacterial count, psychrophilic bacteria and coliform bacteria was greater than that the extracted β-glucan from yeast.